2019
DOI: 10.3776/tpre.2019.v9n1p74-90
|View full text |Cite
|
Sign up to set email alerts
|

How Can They Know What They Don’t Know? The Beliefs and Experiences of Rural School Counselors about STEM Career Advising

Abstract: Many factors contribute to the educational challenges students face in rural areas, including a lack of funding compared to urban and suburban schools and a lack of role models pursuing postsecondary education. School counselors in all settings are trained to provide education to students about the postsecondary options in demand. College and career counseling with students and families in rural areas requires unique understanding of the rural characteristics that shape community life and family dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…This result is consistent with results of Chachashvili et al [71], they found those students who live in a village have more interest in STEM careers. Peterson et al [76] explained this relation in their work as rural communities believe that STEM education can solve some of their very difficult economic and social problems, therefore most rural students are interested in STEM careers [76,77].…”
Section: Schools Type and Location And Stem Career Interestmentioning
confidence: 99%
“…This result is consistent with results of Chachashvili et al [71], they found those students who live in a village have more interest in STEM careers. Peterson et al [76] explained this relation in their work as rural communities believe that STEM education can solve some of their very difficult economic and social problems, therefore most rural students are interested in STEM careers [76,77].…”
Section: Schools Type and Location And Stem Career Interestmentioning
confidence: 99%
“…In contrast to their city and suburban counterparts, rural and small-town students may encounter fewer college graduates, limited access to high-speed internet, and fewer job opportunities (Carr & Kefalas, 2009;Hunter et al, 2020) although they tend to benefit from close-knit relationships within families, schools, and communities (Byun et al, 2012;Lyson, 2002). Furthermore, prior research has documented that rural students tend to lack opportunities to learn (OTL) in STEM, including limited access to advanced math coursework (Anderson & Chang, 2011;Irvin et al, 2017;Reeves, 2012) and STEM-oriented career-advising support (Grimes et al, 2019). Although existing work has documented limited STEM OTL for rural students, it is still unclear how OTL in STEM are longitudinally associated with STEM career aspirations and postsecondary STEM degree enrollment for rural students.…”
mentioning
confidence: 99%
“…There may be differences in the college counseling that is able to be offered in rural high schools, which are important factors in predicting college enrollment (Engberg & Gilbert, 2014 ). Counselors in rural areas have challenges of opportunities and resources (Grimes et al, 2019 ) even as they have more responsibility for college advising relative to other locales because many colleges do not visit rural schools (Salazar et al, 2021 ) and college access organizations and related activities like FAFSA workshops are more often in urban or suburban areas. Rural schools, many of which are small and have high proportions of low-income students, are less often able to provide a robust college-preparatory curriculum (Brown & Schafft, 2011 ; Koricich et al, 2018 ).…”
Section: Influences On College Enrollment For Rural Studentsmentioning
confidence: 99%